Labour Market - Post Keynesian Perspective - Bludnik , Izabela (Studia Oeconomica Posnaniensia, 2014)
Post Keynesian perspective concerning the behavior of the labour market is at odds with the one supported for years by mainstream economics repleted with strong neoclassical influences. Post Keynesians introduce into their analyses such factors as fundamental uncertainty, effective demand, money, segmented labour market, social conflicts, discrimination, hierarchy, customs, and fairness, making a vision of the economic environment much more complicated and attached to the reality. Unemployment is treated neither as a problem arising from the relations observed in the labour market alone, nor as a voluntary phenomenon maximizing the utility of a non-hired agent. In effect, Post Keynesianism differs from the orthodox approach in its understanding of the authorities’ role, political goals and the ways of their realization.